2020
DOI: 10.1177/2048872620907322
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of D-dimer in predicting venous thromboembolism and acute aortic dissection

Abstract: Background: D-dimer is elevated in a variety of conditions. The purpose of this study was to assess the positive predictive value of D-dimer to rule in patients with confirmed pulmonary embolism, deep vein thrombosis, acute aortic dissection or thrombosis of the upper extremity in comparison to patients with elevated D-dimer for other reasons. Methods and results: We studied 1334 patients presenting to the emergency department with pulmonary embolism ( n=193), deep vein thrombosis ( n=73), acute aortic dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
2
33
2
1
Order By: Relevance
“…Our finding found that the levels of plasma D-dimer in patients with psychosis significantly increased, which was consistent with other studies [29,30]. The increased levels of D-dimer in excess of the upper threshold well indicate the possibility of an undetected thromboembolism [31]. Considering the D-dimer test lack of specificity, however, it needs further advanced measurements to evaluate VTE in order to decrease the rate of false-positive results [32].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding found that the levels of plasma D-dimer in patients with psychosis significantly increased, which was consistent with other studies [29,30]. The increased levels of D-dimer in excess of the upper threshold well indicate the possibility of an undetected thromboembolism [31]. Considering the D-dimer test lack of specificity, however, it needs further advanced measurements to evaluate VTE in order to decrease the rate of false-positive results [32].…”
Section: Discussionsupporting
confidence: 91%
“…Elevated D‐dimer level is a sign of excessive coagulation activation and hyperfibrinolysis. Therefore, D‐dimer is often used to detect active thrombus with high sensitivity but low specificity 16 . But, if 3.0 µg/mL was used as the cut‐off value, the sensitivity, specificity, and NPV were 76.9%, 94.9%, and 92.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, D-dimer is often used to detect active thrombus with high sensitivity but low specificity. 16 But, if 3.0 µg/mL was used as the cut-off value, the sensitivity, specificity, and NPV were 76.9%, 94.9%, and 92.5%, respectively. After receiving anticoagulant therapy, the level of D-dimer decreased gradually, which means that D-dimer can not only predict thrombosis but also monitor the effectiveness of anticoagulants.…”
Section: Re Sults and Discussionmentioning
confidence: 97%
“…Elevated D-dimer levels indicate coagulation activation and subsequent hyper fibrinolysis. Therefore, D-dimer is generally used to detect an active thrombus with a high sensitivity but low specificity [ 11 ]. In clinical practice, a D-dimer of less than 0.5 μg/ml is used to rule out VTE [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%